2005
DOI: 10.1111/j.1532-5415.2005.53572.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetaminophen on Behavior, Well‐Being, and Psychotropic Medication Use in Nursing Home Residents with Moderate‐to‐Severe Dementia

Abstract: Untreated pain inhibits activity in nursing home residents with moderate-to-severe dementia. Pain treatment in this group may facilitate engagement with the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 20 publications
3
98
1
2
Order By: Relevance
“…However, analgesia is associated with better proxy-rated QoL, measured with ADRQL, in nursing home patients with advanced dementia [Cordner et al 2010]. This is in agreement with the results of a randomized, double-blind, placebo-controlled, crossover trial, which has shown that the administration of paracetamol 3 g/day to patients with moderate to severe AD in nursing homes results in increased social interaction and engagement with environment versus patients who received placebo [Chibnall et al 2005].…”
Section: Analgesicssupporting
confidence: 83%
“…However, analgesia is associated with better proxy-rated QoL, measured with ADRQL, in nursing home patients with advanced dementia [Cordner et al 2010]. This is in agreement with the results of a randomized, double-blind, placebo-controlled, crossover trial, which has shown that the administration of paracetamol 3 g/day to patients with moderate to severe AD in nursing homes results in increased social interaction and engagement with environment versus patients who received placebo [Chibnall et al 2005].…”
Section: Analgesicssupporting
confidence: 83%
“…In a randomized, double-blind, placebo-controlled cross-over trial Chibnall et al (2005) evaluated the effect of acetaminophen on behavior, emotional wellbeing, and use of as-needed psychotropic medications in 25 NH patients with moderate-to-severe dementia. Twenty-five patients received 4 weeks acetaminophen 1 g  3/day and 4 weeks placebo in random order with a 1-week wash-out period; 23 patients completed both study phases.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were cross-over trials (Manfredi et al, 2003;Chibnall et al, 2005), including only 25 and 47 patients, and only one study recruited subjects with agitation at baseline (Manfredi et al, 2003). The third study was larger, but only a small proportion received analgesics.…”
Section: Discussionmentioning
confidence: 98%
“…This work is supported by one RCT which showed improvement in activities in people receiving paracetamol for 4 weeks compared with placebo. 54 The importance of ADL in pain detection and monitoring warrants further investigation.…”
Section: Growing Pointsmentioning
confidence: 99%